FACULTY PERFORMANCE EVALUATION SYSTEM OF STATE UNIVERSITIES AND COLLEGES IN THE PHILIPPINE EASTERN VISAYAS REGION - Donald Patimo (LPPM Universitas Negeri Jakarta, 2020)
The main concern of this study was the assessment of the faculty performance evaluation system of State Universities and Colleges in the Philippine Eastern Visayas Region. Specifically, the study sought answers to research questions on how the faculty performance is evaluated with regards to evaluation procedures, instruments, and criteria and what is the present and desired faculty performance evaluation system considering the standards on utility, feasibility, propriety, and accuracy. In search of answers to the abovementioned research questions, the researcher made use of the descriptive-assessment research design. The respondents of this study were administrators, faculty members, and students from the main campuses of State Universities and Colleges in Philippine Eastern Visayas Region. As result, the researcher found out that the most common evaluation procedure used were administrative observation in the class and the administration of appraisal instrument. Rating scales were extensively employed evaluation instrument and the most commonly used evaluation criteria were teaching commitment, mastery of the subject matter, teaching for independent learning, and classroom management. In addition, the SUCs in the Eastern Visayas Region of the Philippines unanimously expressed their desire to implement a faculty performance evaluation system that adheres to the standards of utility, feasibility, propriety, and accuracy. At the present, the existing faculty performance evaluation system of SUCs in the Eastern Visayas Region of the Philippines generally followed the standards on utility, feasibility, propriety, and accuracy.